Invasive giant knotweed (Fallopia sachalinensis) alters the composition of oribatid mite communities - Skubała, Piotr (Biological Letters, 2013)
Plant invasions are a serious global threat to biodiversity and ecosystem stability. The invasive giant knotweed Fallopia sachalinensis (synonym: Reynoutria sachalinensis) is one of the most aggressive plant invaders in many countries. It forms dense stands that prevent other species from growing. To assess the impact of the knotweed, oribatid mite communities were studied under Fallopia-free native vegetation and at Fallopia-infested sites (2 types: 90-100% and 30% of coverage) with similar soil. All the sites are located in mixed forest in the Kraków-Częstochowa Upland (Jura Krakowsko-Częstochowska) in south Poland. Species composition and functional group composition of oribatid mite communities were compared. In total, 1540 specimens belonging to 70 oribatid species were collected from 90 soil samples. This successful exotic invasive species had a moderate influence on species richness (20% less species at the totally invaded site than at the Fallopia-free site) and a profound effect on soil oribatid mite community composition. Several oribatid species characteristic of a particular site were observed. Shifts were detected in proportions of groups with different habitat specificity (e.g. higher proportion of eurytopic mites at invaded sites), ecomorphological groups (e.g. lower proportion of litter-dwelling mites at invaded sites), trophic groups (e.g. lower proportion of macrophytophagous mites at invaded sites) and zoogeographical groups (e.g. higher proportion of mites with broad geographical distribution at invaded sites). These observations prove the radical negative change of environmental conditions for soil oribatid mites as a result of Fallopia invasion. The increase in sexually reproducing oribatid mites at invaded sites suggests that this way of reproduction is preferable when resources are in shortage.